LAYOUT AND LINE BALANCING ANALYSIS OF FROZEN COOKED OCTOPUS PRODUCTION FACILITIES (CASE STUDY AT PT ZYZ, FISH FREEZING) - Sumartini, Sumartini; Suryono, Muh; Ratrinia, Putri Wening; An-nissa, An-nissa (Politeknik Kelautan dan Perikanan Dumai, 2023)
Layout is planning for the placement of facilities, equipment, machines, workers, and the flow of the production process by maintaining the efficiency and effectiveness of the production process. Track balance) is a collection of work into work stations so as to get the balance of each workstation. The purpose of the implementation of the WorkPractice This End (KPA) is to analyzeLayout andLine Balancing Production facilities at PT ZYZ. The method used in WorkPractice Final (KPA) is a quantitative descriptive and collection techniques that include observation, interviews, and literature. Work resultPractice Final (KPA) is the calculation of the balance of the line in the production process cut giant octopus at PT ZYZ using the method line balancing it can be seen that the value efficiency the line balance at PT ZYZ is 99% and there is a delay of 1%. With a 1% delay, the flow pattern applied at PT ZYZ is quite efficient. And it can be concluded that the expected efficiency value is 100% in the calculation results. It can be seen that the efficiency value is 99% which indicates the level of work efficiency on the production line.